Issues at the Rural-Urban Fringe: Land Use -- Agricultural Districts - Rodney L. Clouser (EDIS)
This fact sheet is one in a series intended to familiarize readers with land use issues at the rural-urban fringe. Several of the fact sheets specifically address techniques used in various states, including Florida, to encourage the long-term stability of land in agricultural production. Many states use more than one technique in an attempt to prevent land from converting from agricultural to non-agricultural use. Other techniques used to sustain agricultural land, explicitly addressed in forthcoming fact sheets, include Fee Simple Purchase and Purchase of Development Rights, Transfer of Development Rights, Clustering of Development, and Conservation Easements. Other fact sheets addressing rural-urban land use issues are available through the UF/IFAS Electronic Data Information System (EDIS) at http://edis.ifas.ufl.edu. This is EDIS document FE555, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. This document is one of a series entitled "Issues at the Rural-Urban Fringe". Published October 2005.